Screening of Phytochemicals and Antibacterial Property of Medicinal and Aromatic Plants of Nepal - Ghimire, Pragya; Thapa, Suchitra (Amrit Journal, 2024)
Medicinal and aromatic plants (MAPs) are gaining much attention as alternative therapy due to constant failure of chemotherapeutic agents. So, this study was conducted to screen the presence of different phytochemicals in MAPs and assess their antibacterial activity. For this, 4 different medicinal plant (Ocimum sanctum, Acorus calamus, Artemisia vulgaris and Tinospora cordifolia) were collected and extract was prepared. Phytochemical screening was done by chemical test. While antibacterial property was screened by agar well diffusion method against Escherichia coli and Staphylococcus aureus. The phytochemical tests revealed the presence of tannin and alkaloid in O. sanctum only; saponin in A.calamus, T.cordifolia and A.vulgaris; flavonoid in both O.sanctum and A.vulgaris; while phenol in O.sanctum, A.calamus and A.vulgaris. The antibacterial test revealed that O. sanctum, A.calamus and A.vulgaris inhibited the growth of both E. coli and S. aureus whereas T.cordifolia was the least inhibitory against both. Extracts of O.sanctum, A.calamus and A.vulgaris showed larger zone of inhibition (ZOI) against S. aureus than E. coli. Thus, it is concluded that selected medicinal plants possess one or more phytochemicals and can exhibit better antibacterial activity against S. aureus than E. coli, but a stratified analysis of each component is needed for a comprehensive knowledge.